2012
DOI: 10.1016/j.jhydrol.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

An isotope study of the sources of nitrate in Malta’s groundwater

Abstract: SUMMARY, respectively, and even higher in the younger groundwaters of the perched aquifers on Malta (37 mg NO 3 -N L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Many detailed studies have documented the sources and transformation of nitrate in groundwater and rivers, using dual isotope analyses (Mayer et al , ; Silva e t al. , ; Pardo et al , ; Liu et al , ; Panno et al , ; Wexler et al , ; Heaton et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Many detailed studies have documented the sources and transformation of nitrate in groundwater and rivers, using dual isotope analyses (Mayer et al , ; Silva e t al. , ; Pardo et al , ; Liu et al , ; Panno et al , ; Wexler et al , ; Heaton et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…NO 3 − -N, NO 2 − -N, NH 4 + -N, and TN were analyzed by a flow-injection analyzer (HACH Quick chem 8500S2, Hach Company, Loveland, CO, USA). The solid samples were centrifugal oscillated and filtered (0.3 µm) before hydrochemical analysis [34]. The analytical precision was less than ±3%.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…In the European Union (EU), a study has shown that the nitrogen leaching to groundwater derived from agricultural activities results in a general surplus in EU-27 member-states [30]. Groundwater pollution due to agriculture-derived pollutant loads has been studied around the world [31][32][33][34], and high nitrogen loads may result both from the application of fertilizers and from the leaching of grazed pasturelands [35,36].…”
Section: Introductionmentioning
confidence: 99%